Targeted resequencing for analysis of clonal composition of recurrent gene mutations in chronic lymphocytic leukaemia. (27th August 2013) - Jethwa, Alexander; Hüllein, Jennifer; Stolz, Tatjana; Blume, Carolin; Sellner, Leopold; Jauch, Anna; Sill, Martin; Kater, Arnon P.; te Raa, G. Doreen; Geisler, Christian; van Oers, Marinus; Dietrich, Sascha; et al.
Summary: Recurrent gene mutations contribute to the pathogenesis of chronic lymphocytic leukaemia (CLL). We developed a next‐generation sequencing (NGS) platform to determine the genetic profile, intratumoural heterogeneity, and clonal structure of two independent CLL cohorts. TP53, SF3B1, and NOTCH1 were most frequently mutated (16·3%, 16·9%, 10·7%). We found evidence for subclonal mutations in 67·5% of CLL cases with mutations of cancer consensus genes. We observed selection of subclones and found initial evidence for convergent mutations in CLL. Our data suggest that assessment of (sub)clonal structure may need to be integrated into analysis of the mutational profile in CLL.